(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1923)
The ruined castle survives mainly as foundations, none of the walls being more than ten feet high. A ground plan based on careful survey has been produced. The chief feature of this castle appears to have been a great mastertower or keep. The style of construction is typical of the fourteenth-and fifteenth-century castles in Aberdeenshire, marked by the very free use of mortar in filling the interstices between the large irregular stones. Small flat pinnings inserted horizontally, which are so characteristic a feature in sixteenth-century work, are here totally absent. The surviving elements and the surrounding topography are considered along with documentary evidence.